Porous ceramics as backing element for high-temperature transducers - Amini, Mohammad (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2015)
A new application of porous ceramics as the attenuative backing element in high-temperature transducers is introduced. By introducing pores of different volume fractions and various sizes into the ceramic matrix, acoustic impedance and attenuation can be controlled to match their optimal values as predicted by a simple numerical model of the entire transducer, coupled with a model of the attenuative effect of the pores. This concept was applied to the design and manufacture of porous 3mol% Yttria-stabilized zirconia (YSZ) backing elements for a 2.8-MHz lithium niobate (LiNbO3) piezoelectric crystal, with a targeted operating temperature of 700°C to 800°C. Acoustic measurements revealed that the actual acoustic impedance and attenuation of the porous samples matched well with their predicted values. The design and fabrication process can be employed in manufacturing backing elements for a variety of transducers with specified center frequency and signal bandwidth